Experiences, issues, and challenges of Chinese independent documentary, filmmakers in the production of Chinese independent documentary films - Wang, Anting (2024)
Chinese independent documentary films have become vital in reflecting social realities and cultural diversity in China. However, they still lack recognition and support from both the government and the mainstream film industry. Since 2012, successive closures of three major independent film festivals have deepened the crisis in independent film production and distribution. The official termination of the China Independent Film Festival (CIFF) in 2020 highlights the significant challenges these filmmakers face, including limited opportunities, political restrictions, funding difficulties, and distribution barriers. These obstacles have made it difficult for Chinese independent documentaries to gain exposure, prompting filmmakers to develop strategies to overcome these difficulties. This qualitative phenomenological study, grounded in Auteur Theory and Framing Theory, explores the key characteristics of Chinese independent documentary development from 2012 to 2022 in amidst restrictive policies and a rapidly changing social environment. It examines the survival status, unique challenges, and strategies employed by filmmakers during this period. The study was conducted in cities such as Beijing, Shenzhen, Hangzhou, Xiamen, and Changsha, with a purposive sampling of 22 experienced independent documentary filmmakers and practitioners, each with more than a decade of experience. Data were collected through in-depth interviews and field notes, followed by thematic analysis using NVivo 14. By expanding on Auteur Theory, this study highlights the collaborative roles of stakeholders such as producers, curators, and critics in shaping the distinctive features of Chinese independent documentaries and aiding their dissemination. Additionally, it deepens the understanding of how framing theory conceptualizes the challenges filmmakers face, offering insight into necessary strategies. The study identified 14 themes and 43 sub-themes, revealing the unique style, challenges, and strategies of Chinese independent documentaries. The findings underscore the critical role these documentaries play as tools for self-expression, despite limited opportunities and external pressures. Research also highlights issues related to film quality, creative mindset, and ethics, which present ongoing challenges for the industry. The study concludes that strategic collaboration, innovation, and a gradual shift in attitudes toward limited commercial investment are essential for the sustainable development of Chinese independent documentaries. Balancing creative autonomy with market adaptation is key to ensuring their continued growth and impact.